Pengaruh Media Sosial Terhadap Efektivitas Pemasaran Produk Pertanian di Era Digital - Pardede, Guido Imanuel (Jurnal Agroteknologi (Agronu), 2025)
Comprehensive digital changes have influenced farmers' patterns in marketing their agricultural products. Social media now plays an important role in the distribution and promotion of agricultural products. This study reviews 14 scientific articles that have been published over the past decade. The study's findings reveal that social media platforms such as WhatsApp, Instagram, and Facebook facilitate the promotion and distribution of agricultural products directly to consumers. However, the effectiveness of digital marketing is greatly influenced by the level of digital literacy and self-efficacy of farmers in using technology. Some of the challenges faced by farmers include limited training, restricted internet access, and low personal confidence in utilizing social media as an electronic trading platform. Therefore, enhancing farmers' capacity through training, mentoring, and community support is crucial to strengthening the success of digital marketing for agricultural products in Indonesia.